Changing patterns of malaria in south-east Scotland: implications for practitioner awareness and prophylactic advice. Issue 795 (January 1992) - Willocks, L.; Jones, M.; Brettle, R.; Welsby, P.; Gray, J.
Abstract : The medical records of all 229 patients with malaria admitted to the Edinburgh City Hospital between 1969 and 1988 were studied retrospectively. A total of 137 were from Africa, 44 from the Indian subcontinent, 19 from the Far East, 18 from New Guinea, 5 from the Middle East and 3 from South America. The number of yearly admissions rose markedly after 1983, mainly due to an increase in Plasmodium falciparum cases. Ninety-four cases (15 with severe parasitaemia) mainly from Kenya and Nigeria were due to P. falciparum infection and 99 to P. vivax. There were no deaths. A seasonal distribution of onset of fever in patients with P. vivax infections originating from the Indian subcontinent showed that most patients presented during the summer. Prophylaxis had generally been irregular or non-existent but many compliant patients may have been receiving an inadequate dose of chloroquine on a mg/kg body weight basis. General practitioners are likely to see at least one case of malaria every 4 years. They are encouraged to seek advice from a specialist unit whenever necessary whether before or after their patient travels abroad. Travellers, in particular to Kenya and Nigeria, and Asian immigrants to the UK returning on holiday to their country of origin should be strongly advised to take regular prophylaxis including on return to the UK.